Defects, Diffusion and Dopants in Sillimanite - Iyngaran, P.; Sukumar, R.; Kuganathan, N.; Chroneos, A. (Published by MDPI, 2020)
Aluminum silicate based mineral “Sillimanite” (Al2SiO5) is important in the industrial preparation of aluminum-silicon alloys and cement. In the present study classical pair potential simulations are used to examine the intrinsic defect processes, diffusion pathways of Al3+ and O2− ions together with their activation energies and promising dopants on the Al and Si sites in Al2SiO5. The cation anti-site (Al-Si) defect cluster is calculated to be the most favorable defect, highlighting the cation disorder in this material, in agreement with the experiment. The cation disorder is important as this defect can change the mechanical and chemical properties of Al2SiO5. The Al3+ ions and O2− ions migrate in the c direction with corresponding activation energies of 2.26 eV and 2.75 eV inferring slow ion diffusion. The prominent isovalent dopants on the Al and Si sites are found to be the Ga and Ge, respectively, suggesting that they can be used to prevent phase transformation and tune the properties of sillimanite.
Keywords: Sillimanite; Defects; Dopants; Diffusion; Solution energy